PENGUATAN KAPASITAS ORGANISASI PUBLIK DALAM UPAYA MENINGKATKAN PAJAK DAERAH KABUPATEN KARIMUN - Fitri Luthfiyah; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Strengthening the capacity of public organizations must be a joint commitment between the central, provincial and local governments. In general, the goal of capacity strengthening is that individuals, organizations, and existing institutional systems can be used effectively and efficiently to achieve the goals of individual apparatuses and regional institutions. Local taxes are mandatory contributions to regions that are owed by individuals or entities that are compelling. However, the target for the realization of the Karimun regency's tax revenue has decreased every year, so in this case it is necessary to strengthen the capacity in improving public organizations. The concept used is the Wheelen theory, namely there are three indicators: structure, culture, resources. This research uses qualitative research with a phenomenological approach and the required data, both primary and secondary, are obtained by observation, interview and documentation techniques. The results of this study are the first to strengthen the capacity of public organizations in an effort to increase local taxes in Karimun district, which has not been maximized, while the efforts made by the Meranti Regency Regional Revenue Agency are to innovate the structure in the organization related to organizational programs, empower human resources with training and education the number of tax data collection officers, the lack of knowledge of taxpayers about tax paying regulations. The two inhibiting factors for strengthening the capacity of public organizations in an effort to increase local taxes, namely: Not optimal innovation made by the Meranti Regency Regional Revenue Agency, limited human and material resources, large working areas and obstructed from access and distance between islands and the existence of Inaccurate data on taxpayers and objects. Keywords: Strengthening Capacity, Public Organizations and Local Taxes